2024
DOI: 10.3390/plants13020309
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals Key Genes Involved in the Response of Pyrus betuleafolia to Drought and High-Temperature Stress

Panpan Ma,
Guoling Guo,
Xiaoqian Xu
et al.

Abstract: Drought and high-temperature stress are the main abiotic stresses that alone or simultaneously affect the yield and quality of pears worldwide. However, studies on the mechanisms of drought or high-temperature resistance in pears remain elusive. Therefore, the molecular responses of Pyrus betuleafolia, the widely used rootstock in pear production, to drought and high temperatures require further study. Here, drought- or high-temperature-resistant seedlings were selected from many Pyrus betuleafolia seedlings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The transcriptome of low-phosphorus-stressed wheat revealed that TaWRKY74s is the major gene involved, which may regulate plant adaptation to low-phosphorus stress through ABA and auxin signaling [ 30 ]. In Pyrus betulifolia , the PbWRKY gene responds to both high temperature and drought stress and exhibits a high expression trend [ 31 ]. The transcriptome of Gossypium anomalum seedlings revealed that the GaWRKY gene is involved in salt stress response, and was validated via qRT-PCR to be consistent with RNA-seq data [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The transcriptome of low-phosphorus-stressed wheat revealed that TaWRKY74s is the major gene involved, which may regulate plant adaptation to low-phosphorus stress through ABA and auxin signaling [ 30 ]. In Pyrus betulifolia , the PbWRKY gene responds to both high temperature and drought stress and exhibits a high expression trend [ 31 ]. The transcriptome of Gossypium anomalum seedlings revealed that the GaWRKY gene is involved in salt stress response, and was validated via qRT-PCR to be consistent with RNA-seq data [ 32 ].…”
Section: Resultsmentioning
confidence: 99%